Feasibility Analysis of Lettuce, Pakcoy, Celery, and Hydroponic Pagoda Farming Based on R/C Ratio and BEP (Case Study: Sansan Farm, Sukabumi City): Analisis Kelayakan Usahatani Selada, Pakcoy, Seledri, dan Pagoda Hidroponik Berdasarkan R/C Ratio dan BEP (Studi Kasus: Sansan Farm, Kota Sukabumi) - Sevia Maharani; Amalia Nur Milla; Reny Sukmawani (Jurnal Ilmiah Manajemen Agribisnis, 2026)
This study aims to analyze the feasibility of hydroponic vegetable farming at Sansan Farm, Sukabumi City, West Java. The study employed a quantitative method with a descriptive and analytical approach. Data were collected through interviews and questionnaires with the business owner, supplemented by secondary data from relevant literature. The analysis covered production costs, revenue, income, Break-Even Point (BEP), and R/C Ratio. The results show that Sansan Farm generated monthly revenue of IDR 3,045,000, with production costs of IDR 1,875,250, yielding a net income of IDR 1,169,750. The R/C Ratio was 1.62, indicating that every IDR 1.00 spent generates IDR 1.62 in revenue. Furthermore, actual exceeded the BEP of 28,69 kg/month, confirming that the business operates above the loss threshold. Therefore, hydroponic vegetable farming at Sansan Farm is considered feasible, profitable, and has strong prospects for sustainable development.